(untitled) (Research, Society and Development, 2020)
This work is the result of a Master’s research in Mathematical Education conducted with forty students from PROEJA, distributed in three campuses of a Federal School in the city of Rio de Janeiro. The research was conducted with students who were newcomers to the institution and aimed to develop and apply a self-assessment model that would guide teachers in the planning of classes and pedagogical and curricular activities to be worked on during subsequent semesters. In addition to providing students with the opportunity to reflect on their schooling, the importance of cooperative work and attitudinal and conceptual issues in mathematics classes. The article presents in its scope details on the methodological paths, based on action research, and on the questions used. The results showed that, for this group, the instrument can be used to guide the teaching work, besides being important for a reflection of the subjects facing the attitudes and mathematical concepts.